Qadimisme versus Jadidisme dan Dinamika Ulama di Asia Tengah - Ah. Fawaid (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2017)
This article attempts to answer two questions: how is the genesis of Islam in Central Asia and how is the dynamics of ‘ulama related to the fragmentation of qadimism and jadidism. There is no doubt that ‘ulama played important role in spreading Islam and Islamic civilization, including in Central Asia. They got involved in the process of diversification of Islamic teaching and contributed to the struggle against colonialism. However, with modernity the ‘ulama underwent fluctuative relation with each other. Diverse responses to modernity resulted in the diversity of ways of actualization in coping with social problems. The rise of jadidism that was reacted by qadimism constituted a modern phenomenon in Central Asia when the ulama attempted to respond modernity. The diversity of ways of actualization caused the relation between qadimism and jadidism problematic. On another occasion, however, the ulama could contribute to each other, especially when they shared the same interest.